Estrategias de marketing en la Panadería “Amy Y Jumy” de la ciudad de Babahoyo, periodo 2022. - Meléndez Alemán, Melanie Denisse (2023)
Through the present case study called "Marketing strategies in the Amy and Jumy bakery in the city of Bababoyo, period 2022" is related to the line of research "Financial, Administrative, Tax, Audit and Control Management" and the sub- line of the career "Marketing and commercialization", its objective is to evaluate the factors that affect the marketing strategies of the bakery "Amy y Jumy", collecting precise information on the current position of the company. For the development of the work, It required identifying the weaknesses that occur in the company, such as deficiencies in marketing strategies, lack of advertising and promotions, which is why the company wants to optimize the marketing process. To demonstrate the circumstances that gave rise to these events, the analytical method with quantitative variables was used, which contributed to obtaining information through the survey directed to the customers of the bakery, where it is evident that the establishment had incidents in the commercialization of the products, in conclusion, the problem involves the employees of the entity to be trained in relation to marketing strategies, with the aim of improving the distribution processes of edible goods, which allows the correct functioning in the purchase process -sale.